Detection of Copy Number Imbalance in Canine Urothelial Carcinoma With Droplet Digital Polymerase Chain Reaction. (July 2016) - Mochizuki, H.; Shapiro, S. G.; Breen, M.
Urothelial carcinoma (UC) is the most common neoplasm of the canine urinary tract. Clinical presentation of UC is shared with several other, more common urinary tract disorders, and this often delays diagnosis of the UC. Definitive diagnosis of UC requires histopathologic examination of a biopsy specimen, but the cost and invasiveness for these diagnostic tests often result in most diagnoses being made on the basis of clinical findings, diagnostic imaging, and cytologic examination of urine sediment. Regardless of the diagnostic process used, most UCs currently are not diagnosed until they are at an advanced clinical stage and so are associated with poor prognosis. Improved methods for earlier and less invasive detection are needed. In a previous study, the authors demonstrated the presence of highly recurrent DNA copy number aberrations (CNAs) in canine UC and hypothesized that detection of these CNAs in tumor cells can be used as a molecular diagnostic for UC. In this study, a multiplexed droplet digital polymerase chain reaction (ddPCR) assay was detected to detect and quantify CNAs of specific regions of canine chromosomes 8, 13, 19, and 36. The assay was effective at differentiating 31 neoplastic and 25 nonneoplastic bladder tissues based on copy number, with 100% sensitivity and specificity in tissue samples. CNAs were also detected by ddPCR in 67% (12 of 18) of urine DNA specimens derived from UC patients. The findings show that ddPCR is a useful molecular technique to detect CNAs and may be used as a noninvasive molecular diagnostic test for canine UC.